Characteristics and Outcomes of Patient Transport to the Hospital by Emergency Medical Services (EMS); a Cross-sectional Study - Phungoen, Pariwat; Woon Cheung, Lap; Ienghong, Kamonwon; Apiratwarakul, Korakot (Archives of Academic Emergency Medicine, 2023)
Introduction: To enhance the efficiency, it is essential to understand the patterns of service users and develop policies that facilitate effective personnel and resource management. This study aimed to compare the characteristic and outcomes of patients who were transferred to emergency department (ED) by emergency medical services (EMS) and patients transported by other means. Methods: This retrospective cross-sectional study was conducted at Srinagarind Hospital, Thailand, over a 5-year period from 2017-2021. The baseline characteristics, treatment modalities, and outcomes of patients who were transported to ED using EMS and Non-EMS were gathered and compared using STATA software. Results: The study included 15,501 patients with the median age of 51 (interquartile range (IQR): 23-71) years who were referred by EMS over the five-year period (51.72% male). EMS patients had significantly higher median age (51 (23 - 71) vs. 37 (21 - 60); p < 0.001) with male preference (p < 0.001). In the EMS group, the triage level 1 (need for resuscitation) was higher than the non-EMS group (p < 0.001), most of the patients referred following trauma (p < 0.001), and the frequency of cardiac arrest was considerably higher than non-EMS group (2.54% vs 0.05%; p < 0.001). Patients in the EMS group received a higher number of blood tests (p < 0.001), plain radiographic exams (p < 0.001), computerized tomography (CT) scans (p < 0.001), and complex procedures (p < 0.001) than the non-EMS group. The EMS group had a greater number of hospital admissions (p < 0.001) and intensive care unit (ICU) admissions (p < 0.001) compared to the non-EMS group. The EMS group exhibited a significantly higher mortality rate compared to the non-EMS group (p < 0.001). Conclusion: The population utilizing EMS services had higher median age, higher frequency of emergency cases and trauma related complaint, higher need for treatment interventions and imaging procedures, higher rate of hospital and ICU admissions, as well as higher rate of mortality compared to the non-EMS group.